2017
DOI: 10.1038/nrneph.2017.107
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial energetics in the kidney

Abstract: The kidney requires a large number of mitochondria to remove waste from the blood and regulate fluid and electrolyte balance. Mitochondria provide the energy to drive these important functions and can adapt to different metabolic conditions through a number of signalling pathways (for example, mechanistic target of rapamycin (mTOR) and AMP-activated protein kinase (AMPK) pathways) that activate the transcriptional co-activator peroxisome proliferator-activated receptor-γ co-activator 1α (PGC1α), and by balanci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

21
743
1
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 919 publications
(830 citation statements)
references
References 232 publications
(264 reference statements)
21
743
1
4
Order By: Relevance
“…The proximal tubules secrete xenobiotics into the filtrate and reabsorb glucose, albumin, and various electrolytes via an array of transporters and receptors that can also transport drugs. To generate energy for these processes, proximal tubule cells are rich in mitochondria; thus, proximal tubule cells are also sensitive to disruptions in oxidative phosphorylation 11 . Moreover, metabolic enzymes such as β-lyase, expressed in renal proximal tubule cells, can bioactivate xenobiotics, potentiating the toxicity of these agents.…”
mentioning
confidence: 99%
“…The proximal tubules secrete xenobiotics into the filtrate and reabsorb glucose, albumin, and various electrolytes via an array of transporters and receptors that can also transport drugs. To generate energy for these processes, proximal tubule cells are rich in mitochondria; thus, proximal tubule cells are also sensitive to disruptions in oxidative phosphorylation 11 . Moreover, metabolic enzymes such as β-lyase, expressed in renal proximal tubule cells, can bioactivate xenobiotics, potentiating the toxicity of these agents.…”
mentioning
confidence: 99%
“…57 In the presence of hyperglycemia, the metabolic flux of glucose can be shifted from complete oxidation in mitochondria to the glycolytic pathway, and the deleterious effects of hyperglycemia are considered to be owing mainly to increased activity of five different pathways: pentose phosphate pathway, 8 sorbitol/polyol pathway, 9 advanced glycation end-products pathway, 10,11 protein kinase C pathway, 12 and hexosamine pathway (Fig. 1).…”
mentioning
confidence: 99%
“…Mitochondrial dynamics and biogenesis are crucial processes underlying mitochondrial homeostasis (Mishra & Chan, ). It has been reported that impairment of mitochondrial homeostasis leads to the injury of renal tubular epithelial cells in I/R (Bhargava & Schnellmann, ). Our present results demonstrate that FOXO1 participates in mitophagy, biogenesis and mitochondria‐mediated apoptosis in I/R.…”
Section: Discussionmentioning
confidence: 99%